2001
DOI: 10.1074/jbc.m007936200
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Donor Substrate Conversion in Yeast Transketolase

Abstract: The cleavage of the donor substrate D-xylulose 5-phosphate by wild-type and H263A mutant yeast transketolase was studied using enzyme kinetics and circular dichroism spectroscopy. The enzymes are able to catalyze the cleavage of donor substrates, the first halfreaction, even in the absence of any acceptor substrate The pentose phosphate pathway is a major metabolic pathway in all cells. It consists of a dehydrogenase-decarboxylating system that converts D-glucose 6-phosphate to D-ribulose 5-phosphate, generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Instead, we assessed the effects by direct measurements of the apparent dissociation constant for the substrate analog MAP (K d(MAP) ). The K d(MAP) values for charge-reversed variants E401K and K403E were 129-and 136-fold higher, respectively, than with E1ec ( (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we assessed the effects by direct measurements of the apparent dissociation constant for the substrate analog MAP (K d(MAP) ). The K d(MAP) values for charge-reversed variants E401K and K403E were 129-and 136-fold higher, respectively, than with E1ec ( (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…TK was purified according to the protocol of Wikner et al (17), with modifications as described in ref. 15. Circular Dichroism (CD) Measurements.…”
Section: Methodsmentioning
confidence: 99%
“…1). In the absence of a suitable acceptor substrate, the intermediate decomposes into enzyme-ThDP and glycolaldehyde (15), albeit at a rather low rate. This suggested that it would be possible to establish experimental conditions that would lead to significant steady-state levels of this intermediate in the active site of TK, making its detection by biophysical methods possible.…”
mentioning
confidence: 99%
“…The DYNAFIT method has been used previously (37,38) to characterize complex inhibitory mechanisms. In the example perhaps most relevant to the mechanism proposed for AceAP1, Stanley et al (39) used DYNAFIT to study the inhibition of vitamin K-dependent ␥-glutamylcarboxylase by various polypeptides important in the blood coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%